2006
DOI: 10.1093/deafed/enl003
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Educational Experiences in the Development of Deaf Identity

Abstract: In this study, the analytical educational experiences of 25 deaf adults are explored in relation to their identity. The qualitative analysis indicated that the most critical educational experiences for the participants' identity concerned their interactions with hearing or deaf peers and their language of communication with their peers at school. The participants with a hearing identity attended general schools, where they interacted with hearing peers in Greek, whereas the participants with a Deaf identity at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 28 publications
4
33
0
6
Order By: Relevance
“…They might need support to find out who they are and how to relate to peers. In a state of marginal identity they would feel uncomfortable, and not well accepted within either the deaf or the hearing worlds (Nikolaraizi and Hadjikakou 2006). Children suffering from an identity crisis had high as well as low self-esteem, which supports the hypothesis that the crisis can be a constructive and age-related search for identity or an indication of more complex personal and social problems.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…They might need support to find out who they are and how to relate to peers. In a state of marginal identity they would feel uncomfortable, and not well accepted within either the deaf or the hearing worlds (Nikolaraizi and Hadjikakou 2006). Children suffering from an identity crisis had high as well as low self-esteem, which supports the hypothesis that the crisis can be a constructive and age-related search for identity or an indication of more complex personal and social problems.…”
Section: Discussionmentioning
confidence: 64%
“…they can find themselves in a subordinate position in terms of power (Nordströ m 2002). That HH and deaf children indeed are in a subordinate position, and are excluded in numerous ways at school, has been identified by researchers in many different countries (Andersson and Lawenius 1997;Israelite, Ower, and Goldstein 2002;Kent 2003;Nikolaraizi and Hadjikakou 2006). School experience, the social atmosphere and interaction with other children and teachers are significant factors in moulding the identity of a HH or deaf child.…”
Section: Identity and Self-esteemmentioning
confidence: 98%
“…Nikolaraizi and Hadjikakou (2006) investigated how educational experiences affected the development of hearing, deaf, or bicultural identity by interviewing 25 individuals in Greece. The study found that the deaf person's identity was associated with the type of school attended.…”
Section: Factors Affecting Identity and Life Outcomementioning
confidence: 99%
“…In addition to these areas of focus, this study is important because it recognizes the growing influence of the wealth of research into deaf identity, such as a similar study conducted in Greece by Hadjikakou and Nikolaraizi (2006). To date, no study has been done in South Africa regarding deaf identity.…”
Section: Contextmentioning
confidence: 99%
“…Taking this idea further, Hadjikakou and Nikolaraizi (2006) add that identity is a socially constructed process, which is expanded upon by relating past and present experiences into one's identity, thus being shaped by the narratives or stories that we tell others (Sikes & Gale, 2006). Therefore, this study adopted the narrative approach as used by Leigh (2009) and Stobeck & Magongwa (2006) to explore deaf identities through analysis of the interview transcripts.…”
Section: Deaf Identitiesmentioning
confidence: 99%